Comparison Of Conventional And Modern Wound Care Methods In Diabetes Mellitus Patients - Abdurrahman Abdurrahman; Bustami Bustami; Cut Mutiah; Rezqiqah Aulia Rahmat; Asrianto Asrianto (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Wounds in patients with diabetes mellitus are a common complication and carry the risk of infection and even amputation. Proper wound care is crucial to accelerate healing. Wound care methods include conventional and modern methods, each with distinct characteristics. This study aims to compare the effectiveness of conventional and modern wound care methods in patients with diabetes mellitus. This study used a quasi -experimental design with a comparative study approach . A sample of 60 patients was divided into two groups: the conventional wound care group and the modern wound care group. Data were collected through observation of wound development using a wound assessment sheet. Data were analyzed using an independent t- test . The results of the study showed that the modern wound care group had a faster average healing time compared to the conventional method with a p-value = 0.001 (<0.05) . The conclusion of this study is that modern wound care methods are more effective than conventional methods in accelerating wound healing in diabetes mellitus patients. Keywords: Diabetes Mellitus, Wounds, Modern Wound Care, Conventional Wound Care